The popular handbook on the Rapture - LaHaye, Tim F; Ice, Thomas; Hindson, Edward E (Eugene, Or. : Harvest House Publishers, 2011)
"Why is there so much confusion about how and when the rapture will take place? Will Christians go through the Tribulation or be spared from it? What is next on God's prophetic timetable? More than ever, as world crises escalate, Christians are asking important questions about the rapture and second coming. In their search for answers they're discovering widely divergent views about the end times. Why all the different perspectives? Tim LaHaye, Thomas Ice, and Ed Hindson have brought together a team of respected Bible prophecy experts who look carefully to God's Word for clarity. This resource includes the latest research on rapture teaching, careful Bible scholarship, and answers that give Christians both comfort and hope for the future" --Cover, p. 4
Includes bibliographical references
Keywords: Rapture (Christian eschatology)